PARTISIPASI MASYARAKATDALAM PELAKSANAAN STRATEGI NASIONAL PENCEGAHAN KORUPSI (STRANAS PK) - Andriyansyah, Fahrudin (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
The National Strategy on Corruption Prevention is a national policy direction that contains the direction of focus and targets for corruption prevention which are used as a reference for ministries, agencies, local governments and other stakeholders in implementing corruption prevention actions in Indonesia. The focus of the The National Strategy on Corruption Prevention includes licensing and commerce, state finances, and law enforcement. One of the challenges in the The National Strategy on Corruption Prevention is the lack of community involvement in these 3 focuses. Limited community involvement in these 3 (three) focuses is the background of the importance of strengthening participation of society in the implementation of The National Strategy on Corruption Prevention. Without community involvement in the corruption prevention agenda, the corruption eradication agenda will not run optimally. The Purpose of this researcher is to find how community participation in the implementation Stranas PK. The Research uses normatif law. Community involvement The National Strategy on Corruption Prevention can be done through the stages of formulating, implementing, monitoring, evaluating and reporting The National Strategy on Corruption Prevention.